Réponses

2013-05-14T00:21:44+02:00

si tu mets x =2

 

a) x² +2 = 2² +2 = 4 + 2 = 6

 

b ) (x-2)²= x² - 4x + 4  si x = 2 donc  2² - 4x2 + 4 = 0

 

c ) (x-2)² - 3 = x² -4x +4 -3 = x² - 4x +1 donc  2² -4x2 +1 = -3

 

d )5-3 ( x-2 )² = 5 - 3( x² - 4x +4  )

                      = 5 -3x² +12x -12

                      =  -3x² +12x -7    donc -3 x2² + 12x2 -7  = -12 +24 -7 = 5

 

je pense que c'est ça

bon courage !

 

on peut faire aussi :

 

a) 2²+2 = 4+2= 6

b) (2-2)² = 0

c) ( 2-2)² - 3= -3

d) 5 - 3 (2 -2)² = 5

on trouve les mêmes résultats